2011
DOI: 10.1007/s10344-010-0491-9
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to selected pathogens in wild boar (Sus scrofa) from Catalonia (NE Spain)

Abstract: From 2004 to 2007, blood samples from 273 healthy wild boars (Sus scrofa), culled during the hunting season, were obtained in three areas of Catalonia (NE Spain): Pyrenees,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
33
5
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 26 publications
7
33
5
2
Order By: Relevance
“…The role of wild boars in PCV2 transmission to domestic pigs is not clear (Meng et al, 2009). The prevalence of SIV H1N1 antibodies (9.7% overall) in our study is lower than previously reported (Zupancic et al, 2000), but comparable to that in other European countries (Kaden et al, 2009;Closa-Sebastia et al, 2011). There was no evidence of exposure to SIV in wild boars in neighboring Slovenia (Vengust et al, 2006).…”
Section: Discussioncontrasting
confidence: 54%
“…The role of wild boars in PCV2 transmission to domestic pigs is not clear (Meng et al, 2009). The prevalence of SIV H1N1 antibodies (9.7% overall) in our study is lower than previously reported (Zupancic et al, 2000), but comparable to that in other European countries (Kaden et al, 2009;Closa-Sebastia et al, 2011). There was no evidence of exposure to SIV in wild boars in neighboring Slovenia (Vengust et al, 2006).…”
Section: Discussioncontrasting
confidence: 54%
“…Influenza infections in wild boars were reported in the United States (Gipson et al, 1999;Corn et al, 2009), France (Vittecoq et al, 2012), Germany (Polley et al, 2007;Kaden et al, 2008), Poland (Markowska-Daniel and Pejsak, 1999Markowska-Daniel and Kowalczyk, 2005), and Spain (Vicente et al, 2002;Closa-Sebastia et al, 2011). Our survey is consistent with previous investigations showing that coinfection of H1 and H3 influenza viruses is common in feral swine.…”
Section: Discussionsupporting
confidence: 82%
“…Only a few investigators have examined exposure of feral swine to influenza viruses (Kaden et al, 2008;Closa-Sebastia et al, 2011;Vittecoq et al, 2012). Direct detection of viral antigen in feral swine is difficult because of the short course of the infection.…”
Section: Introductionmentioning
confidence: 99%
“…These prevalence results also showed that in Lithuania there are more wild boars positive for PRRSV antibodies than in Spain (2.0%-3.0%) (4,6) and Germany (3.82%), as it was demonstrated during recent PRRSV serological investigations in these countries (13). This high serological prevalence in the wild boars in Lithuania can be related to the changes in the wild boar population.…”
Section: Discussionmentioning
confidence: 53%